2004
DOI: 10.1589/rika.19.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Elbow Joint Posture on Elbow Flexor Fatigability and Muscle Strength during Isometric Contraction

Abstract: We examined here the effect of the elbow joint posture on elbow flexor fatigability and strength during isometric contraction. Nine healthy subjects, who gave informed consent, participated in the present study. The subjects were seated in a chair with the shoulder joint at 0°, and the shoulders, pelvis, and thigh were immobilized by straps. The elbow joint posture was positioned at 30, 60, 90 and 120° of elbow flexion. First, subjects produced maximal elbow flexion as a maximum voluntary contraction (MVC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Vøllestad [25] reported that muscle fatigue was defined as a decrease in the ability to exert maximum muscle strength with some form of motion. In addition, Higashi et al [26] reported that the 50% MVC isometric contraction task produced recognizable muscle fatigue over the course of time. In this study, the subjects may have been exerting 50% MVC pinch force for 2 min.…”
Section: The Effect Of Motor Imagery On the Accuracy Of Motionmentioning
confidence: 99%
“…Vøllestad [25] reported that muscle fatigue was defined as a decrease in the ability to exert maximum muscle strength with some form of motion. In addition, Higashi et al [26] reported that the 50% MVC isometric contraction task produced recognizable muscle fatigue over the course of time. In this study, the subjects may have been exerting 50% MVC pinch force for 2 min.…”
Section: The Effect Of Motor Imagery On the Accuracy Of Motionmentioning
confidence: 99%
“…Continuous variation of sole pressure refers to the pressure exerted by the sole on the plane inside the shoe. Some studies have shown that plantar pressure measurement is used based on clinical activities, including gait dynamic analysis [1,2] , Alzheimer's patients [3] , type 2 diabetes [4][5][6] , stroke rehabilitation and ankle sprain assessment [5] .…”
Section: Introductionmentioning
confidence: 99%